Necropolis: burial & afterlives in Cape Town - Maggs, Alexander (School of Architecture, Planning and Geomatics, 2023)
Necropolis is a proposal for a public burial and memorial park in Cape Town for obliterated (cremated, aquamated etc) and bone remains. It explores an architecture for the final farewell to the body and spirit of the deceased, and for personal and collective remembrance. In contrast to other South African Cities, Cape Town is unique for the popularity of cremation, which accounted for 40% of recorded burials in 2019. Architectural responses however are often piecemeal. Burial places were once part of cities' symbolic centres, and mortality understood as an inevitable spiritual journey. During modernisation however, they were exiled to cities' peripheries, far from people's everyday lives. The chosen site is in Deer Park, at the edge of the City Bowl, through which runs a perennial stream linked to the city's historical centre. The Park has a varied heritage landscape which the design situates itself beside, together constituting a landscape of remembrance. The programme explores a secular spiritual and sacred response to burial, grief and memory. The architectural language explores a stereotomics of brick, stone and rubble in dialogue with the ground and Earth. The primary methodology is speculative design, through hand sketching, photographing, mapping, collaging, modelling, digital modelling and rendering. Design thinking is supported by a varied literature review: firstly a collection of Cape Town and colonial European burial histories and practices. Secondly, a phenomenology of the ground, geology, and stone and rubble building. Thirdly, precedent studies of sacred and burial architecture, supported by analysis through drawing.